Utilizing Biotechnology for Plant Disease Management: A Comprehensive Review: Utilizing Biotechnology for Plant Disease Management: A Comprehensive Review - Manjot Kaur; Muskan Bhullar; Ramneek Kaur (The Indonesian Forestry Certification Cooperation, 2026)
Threat to agriculture economy from pests and diseases are increasing constantly. Global food crops are lost from 20% to 40% due to pests and diseases, with damage reaching 14.1% by plant diseases, accounting for 220 billion in annual agricultural trade losses. Traditional methods like chemical control have a great detrimental effect on environment. Thus, an alternative concept of Molecular detection techniques and biotechnology sets diagnostic tools, techniques can generate accurate results rapidly enough to be useful for disease management decisions. Biotechnology is the genetic manipulation, and multiplication of any living organism through novel techniques and technologies such as tissue culture and genetic engineering resulting in the production of improved or new organism and products that can be used in variety of ways. The various applications of biotechnology in plant pathology includes, Genetic Resistance, Marker Assisted Breeding, Genetic Engineering, RNA Interference, Gene Pyramiding and tagging of resistant genes.